STRATEGI PROMOSI UNIVERSITAS UNTUK MENARIK PERHATIAN CALON MAHASISWA - Afifah, Hana (DFAME Digital Financial Accounting Management Economics Journal, 2024)
This research aimed to examine the impact of the university's promotional strategy on the enrollment of potential students. The study utilized one-on-one semi-structured interviews with current university students in the Purbalingga area as participants. The number of participants was determined by saturation, and the collected data were transcribed verbatim. The interviews were then analyzed using ATLAS.ti to identify emerging themes. The findings revealed that the most effective promotional strategies for attracting students included printed brochures and Instagram pages, coupled with personal messaging via WhatsApp and direct messages on Instagram. The study suggests that today's university target consumers, Generation Z, appreciate both digital and traditional advertising, as long as it provides clear information, has an aesthetically pleasing design, and offers personal interaction, creating a sense of real engagement without the need to visit the campus.